Kolaborasi Tradisi Begibung Dalam Upaya Pengembangan Daya Tarik Wisata Gastronomi Di Desa Sedau Kabupaten Lombok Barat - Yuli Astuti; Amiluhur Soeroso; Isdarmanto, Isdarmanto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to find out one of the typical Lombok eating traditions, namely the Begibung tradition, in terms of the gastronomic component of the efforts that have been made by 9 stakeholders (Nona Helix) in preserving this tradition, as well as seeing the potential of the Begibung tradition as gastronomic tourism. The method used in this study uses a qualitative descriptive method. This research shows that the Begibung tradition has fulfilled all the elements of gastronomy and identification of the role of stakeholders in developing and making the Begibung tradition a gastronomic tour in the tourist village of Sedau, West Lombok, needs to be improved so that it can better develop the Begibung tradition.